Differential Diagnosis of Small Cell Carcinoma of the Ovary or Ovarian Metastases of Small Cell Carcinoma of the Lung: A Case Report and Review of the Literature - Ester Oneda; Fausto Zorzi; Antonio Gorio; Federico Quaglia; Chiara Abeni; Luigina Rota; Alberto Zaniboni (Case Reports in Oncology, 2020)
Small cell tumors arise from the neuroendocrine cell system and they are most frequently found in the lung (SCLC). Small cell tumor could occasionally arise in other body sites, such as the cervix, prostate, gastrointestinal tract, and very rarely from other sites. Metastatic SCLC patients present with metastatic disease in 80% of cases, and the metastases typically are reported in brain, liver, lung, and bone; they rarely could be found in the ovary. Differently, primitive small cell carcinoma of the ovary of pulmonary type is a rare and highly aggressive tumor arising from the ovarian cells; no suitable treatment strategy has been established yet. In this paper, we talk about a 72-year-old woman who presented with abdominal bleeding and a large mass in her pelvic region. A primary ovarian carcinoma was suspected, and she underwent hysterectomy with laparoscopic surgery and bilateral oophorectomy, lymph node resection, omentectomy, complementary appendix and sigmoid resection. The postoperative pathologic diagnosis was a differential diagnosis between small cell ovarian carcinoma of the pulmonary type and metastasis of SCLC.